Targeting bacterial biofilms via surface engineering of gold nanoparticles. Issue 128 (14th December 2015) - Giri, Karuna; Rivas Yepes, Laura; Duncan, Bradley; Kolumam Parameswaran, Praveen; Yan, Bo; Jiang, Ying; Bilska, Marcela; Moyano, Daniel F.; Thompson, Michael A.; Rotello, Vincent M.; Prakash, Y. S.
Abstract : Bacterial biofilms are associated with persistent infections and antibiotics resistance which substantially complicate patient care. Surface engineering of nanoparticles represents a novel and unconventional approach to disrupt biofilms and target bacterial pathogens. Abstract : Bacterial biofilms are associated with persistent infections that are resistant to conventional antibiotics and substantially complicate patient care. Surface engineered nanoparticles represent a novel, unconventional approach for disruption of biofilms and targeting of bacterial pathogens. Herein, we describe the role of surface charge of gold nanoparticles (AuNPs) on biofilm disruption and bactericidal activity towards Staphylococcus aureus and Pseudomonas aeruginosa which are important ventilator associated pneumonia (VAP) pathogens. In addition, we study the toxicity of charged AuNPs on human bronchial epithelial cells. While 100% positively charged AuNP surface was uniformly toxic to both bacteria and epithelial cells, reducing the extent of positive charge on the AuNP surface at moderate concentrations prevented epithelial cell toxicity. Reducing surface charge was however also less effective in killing bacteria. Conversely, increasing AuNP concentration while maintaining a low level of positivity continued to be bactericidal and disrupt the bacterial biofilm and was less cytotoxic to epithelial cells. These initial in vitro studies suggest that modulation of AuNP surface charge could be used to balance effects on bacteria vs. airway cells in the context of VAP, but the therapeutic window in terms of concentration vs. surface positive charge may be limited. Additional factors such as hydrophobicity may need to be considered in order to design AuNPs with specific, beneficial effects on bacterial pathogens and their biofilms.